Exposure-safety and exposure-efficacy analyses of polatuzumab vedotin in patients with relapsed or refractory diffuse large B-cell lymphoma. Issue 12 (14th October 2020) - Lu, Tong; Gibiansky, Leonid; Li, Xiaobin; Li, Chunze; Shi, Rong; Agarwal, Priya; Hirata, Jamie; Miles, Dale; Chanu, Pascal; Girish, Sandhya; Jin, Jin Yan; Lu, Dan
Abstract: Exposure-response relationships were investigated to assess the risk/benefit of polatuzumab vedotin (pola) + bendamustine-rituximab (pola + BR) in relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). Analyses were conducted in pivotal study GO29365 (NCT02257567; BR/pola + BR/pola + BG [BG: bendamustine-obinutuzumab]; 1.8 mg/kg pola, every 3 weeks [Q3W], six cycles), and supportive studies DCS4968g (NCT01290549) and GO27834 (NCT01691898) (pola/pola + R/pola + G; 0.1–2.4 mg/kg pola Q3W; eight-cycle landmark), separately. Exposure was characterized as simulated cycle-6 AUC and C max for antibody-conjugated mono-methyl auristatin E (acMMAE) and unconjugated MMAE. Supportive studies showed response rate and safety risk (grade ≥2 peripheral neuropathy; grade ≥3 anemia) increased with exposure, suggesting not to dose below 1.8 mg/kg (up to eight-cycle) for balancing safety and efficacy. Pivotal study with limited exposure range showed no exposure-safety relationship and slightly positive exposure (acMMAE)-efficacy relationship for overall survival. The exposure-response analyses and the observed risk/benefit characteristics in pivotal study supported pola (1.8 mg/kg) +BR Q3W for six cycles in R/R DLBCL patients.